Development of a Generative AI Model for Early Detection and Prevention of Electrical Faults in Thermal Power Plants - Shreekantrao; Nagendra Kumar Swarnkar (International Journal of Energy and Thermal Applications, 2026)
Electrical faults in thermal power plants can lead to severe equipment damage, production downtime, and safety hazards if not detected in advance. This study presents the development of a Generative Artificial Intelligence (GenAI) model for the early detection and prevention of electrical faults using predictive analytics. The proposed framework integrates Generative Adversarial Networks (GANs) with deep learning (CNN) and machine learning algorithms (Random Forest, Logistic Regression) to enhance data diversity, improve classification accuracy, and ensure early fault diagnosis. A comprehensive dataset representing operational parameters—such as voltage, current, temperature, vibration level, load factor, and power factor—was utilized for model training and evaluation. Synthetic data generated through the GAN improved fault representation and model generalization. Experimental results demonstrate that the proposed GAN-CNN hybrid model achieved the highest accuracy of 98.3%, outperforming traditional methods in terms of precision, recall, and F1-score. The feature importance analysis revealed that voltage, current, and temperature were the most influential parameters in predicting potential faults. The findings confirm that the developed Generative AI framework provides a robust, data-driven, and proactive solution for predictive maintenance and fault prevention in thermal power plants. This approach not only reduces unplanned downtime but also enhances system reliability, safety, and operational efficiency — marking a significant step toward intelligent and self-healing power systems.
Keywords: Deep Learning; Fault diagnosis; Predictive Maintenance; Thermal Power Plants; generative artificial intelligence